P182 Underlying Causes of Bronchiectasis Identified in a Specialist Non-CF Bronchiectasis Service. (19th November 2012) - Leighton, KE; Stretton, RJ; Furrie, E; Marshall, S; Fardon, TC; Schembri, S; Chalmers, JD
Abstract : Introduction: Identifying the cause of non-CF bronchiectasis can have important implications for future treatment. The British Thoracic Society (BTS) issued guidance for testing in bronchiectasis in 2010 but many of these recommendations are based on expert opinion only (grade D evidence). We describe the underlying causes identified using the BTS recommended testing regime at a specialist non-CF bronchiectasis service. Methods: The study included patients attending a tertiary bronchiectasis clinic over 1 year (April 2011-April 2012). The diagnosis of bronchiectasis was made by high resolution CT. Sputum microbiology for the previous 2 years was used to determine colonisation status. A respiratory physician and immunologist assigned the underlying cause after discussion, following standardised testing recommended by the BTS guidelines. Results: 88 patients had CT confirmed bronchiectasis. The median age was 66 years (Interquartile range 57–73). 39 patients (44.3%) were male. The median number of lobes involved on CT was 2 (IQR 1–3). 51 patients were classified as idiopathic. 14 patients had ABPA, 8 patients had connective tissue disease, 4 patients were classified as post-infective, 3 patients had inflammatory bowel disease, 3 patients had an identified immunodeficiency, 2 were classified as secondary to COPD, 1 patient had chronic reflux, 1 patient had a congenital malformation and 1 patient had Mounier-Kuhn syndrome. In the idiopathic cohort, 19 patients were colonised with Haemophilus influenzae, 7 with Streptococcus pneumoniae, 7 with Pseudomonas aeruginosa, 4 with Moraxella catarrhalis, 3 with Staphylococcus aureus and 5 patients with enteric gramme negative organisms. The remainder were not colonised. In patients with an identified cause, 12 patients had H. influenzae, 5 had enteric gramme negative organisms, 4 had P. aeruginosa, 3 had M. catarrhalis, 2 had S. aureus and 1 patient had S. pneumoniae . None of the frequencies of organisms were significantly different between idiopathic and non-idiopathic groups (p>0.05 for all comparisons). Conclusion: An underlying cause of bronchiectasis could be identified in 42% of cases of non-CF bronchiectasis using the recommended testing protocol from the British Thoracic Society bronchiectasis guidelines. This emphasises the importance of testing for underlying disorders in bronchiectasis patients attending secondary care.